2011
DOI: 10.1080/15401383.2011.560076
|View full text |Cite
|
Sign up to set email alerts
|

Artistic Representation: Promoting Student Creativity and Self-Reflection

Abstract: The authors conducted a qualitative study on the use of artistic representation to promote students' creativity and enhance their ability to self-reflect. The researchers used self-reflection articles about artistic representation and responses to a questionnaire at the end of the semester. Three overarching themes, as seen through the lens of the researchers, were: a) influences on self-reflection, b) emotions elicited during the creative process and classroom presentation, and c) responses following completi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Research results demonstrated that activities requiring creative thinking resulted in positive outcomes. They enhanced students' self-reflection (Autry & Walker, 2011), increased advanced thinking skills (Hargrove, 2011), and strengthened collaboration with others (Crow, 2008). Thus, it is vital to provide activities such as PBL for students to improve their creativity in formal and/or informal learning environments.…”
Section: Creativitymentioning
confidence: 99%
“…Research results demonstrated that activities requiring creative thinking resulted in positive outcomes. They enhanced students' self-reflection (Autry & Walker, 2011), increased advanced thinking skills (Hargrove, 2011), and strengthened collaboration with others (Crow, 2008). Thus, it is vital to provide activities such as PBL for students to improve their creativity in formal and/or informal learning environments.…”
Section: Creativitymentioning
confidence: 99%
“…Self-reflection is a useful tool through which the practitioner continually explores personal belief systems, which influence their perceptions of clients (Autry and Walker, 2011; Pompeo and Heller Levitt, 2014), and has long been considered an important aspect of professional development (Mandell, 2008). A lack of awareness of one’s own feelings and reactions to a family could lead to burn-out as well as abuse of one’s power (Mandell, 2008).…”
Section: Current Knowledge and Child Protection Practicementioning
confidence: 99%